Design and Implementation of a Web-Based Online Exam System with Screen Monitoring for Academic Integrity - Rachael Davis; Robbi Rahim (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2025)
The widespread use of online exams has exacerbated academic integrity issues due to limited visibility of proctoring in a digital environment. This study designed and implemented a web-based exam system that integrates screen-monitoring features to support transparency in proctoring between proctors and students. The system was developed using a Waterfall approach, encompassing needs analysis, system design, implementation, and functional testing. System evaluation was conducted through a limited pilot test involving 4 participants, with quantitative data obtained from system logs that recorded successful answer saving, exam time control, tab-switching detection, and real-time screen monitoring. Descriptive analysis showed that 100% of participants' answers were saved without data loss, all exam sessions ended with automatic access lockout, and tab-switching activity was detected and acted upon with up to 3 warnings before the exam was disabled. The screen monitoring feature operated stably under standard internet network conditions, although performance was affected by user bandwidth. These findings confirm that integrating screen monitoring into online exam systems is a viable, globally replicable proctoring solution, particularly for educational institutions that require technology-based academic integrity mechanisms without relying on complex AI-based proctoring.